THE PRECAUTIONARY IN CRIMINAL ENFORCEMENT - Arion Escorsin de Godoy (Revista Eletrônica do Curso de Direito da UFSM, 2014)
This paper discusses the adoption of personal protective measures by Magistrates under the criminal enforcement. Therefore, the theoretical definition of the general power of caution and its application to criminal proceedings, both at the stage of knowledge, as is done in enforceable. It focuses, however, with particular emphasis on precautionary suspension of parole and injunctive regression regime of imprisonment, as well as the management of that power for the benefit of the convict. The methodology is hermeneutic, with the referential judgments, legislation and doctrine.